2014
DOI: 10.1186/1756-0500-7-682
|View full text |Cite
|
Sign up to set email alerts
|

Mining rich health data from Canadian physician claims: features and face validity

Abstract: BackgroundPhysician claims data are one of the largest sources of coded health information unique to Canada. There is skepticism from data users about the quality of this data. This study investigated features of diagnostic codes used in the Alberta physician claims database.MethodsAlberta physician claims from January 1 to March 31, 2011 are analyzed. Claims contain coded diagnoses using the International Classification of Diseases, 9th revision (ICD-9), procedures, physician specialty and service-fee type. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 25 publications
(23 reference statements)
0
41
0
Order By: Relevance
“…These three population-based datasets are routinely used in Canada to conduct health services research. Validation studies have shown them to have excellent sensitivity and specificity for identifying colorectal-related procedures and have high face validity for diagnosis codes [14–16]. Health services related to CRC diagnosis were defined using both procedure and diagnosis codes.…”
Section: Methodsmentioning
confidence: 99%
“…These three population-based datasets are routinely used in Canada to conduct health services research. Validation studies have shown them to have excellent sensitivity and specificity for identifying colorectal-related procedures and have high face validity for diagnosis codes [14–16]. Health services related to CRC diagnosis were defined using both procedure and diagnosis codes.…”
Section: Methodsmentioning
confidence: 99%
“…Of those who responded to the follow-up survey (n = 63), 44 (69.8%) were males and 19 (30.1%) were females. Respondents to this follow-up survey were from the following specialties: internal medicine (22, 35.0%), general surgery (18, 28.6%), neurology/neurosurgery (2, 3.0%), pediatrics (11,17.5%) and psychiatry (10, 15.9%). Of the 317 consenting physicians, 38.1% were reimbursed by fee for service, 14.1% by a partial alternative payment plan and 47.8% by full alternative payment plan.…”
Section: Resultsmentioning
confidence: 99%
“…A study evaluating physician claims data found high face validity; however, further validation work is still needed to assess provincial variation in the quality of these data. 17 We extracted all services provided by these physicians from Jan. 1, 2002, to Dec. 31, 2009. The linked records formed the denominator (i.e., standard reference; number of services provided by physicians).…”
Section: Outcomes and Sources Of Datamentioning
confidence: 99%
“…Because of universal health care in Canada, a very large proportion of health care visits are captured in administrative settings such as physician claims [13]. In our jurisdiction ProvLab performs the majority of tests for many notifiable diseases and since 2004 performs all pertussis testing for the province.…”
Section: Discussionmentioning
confidence: 99%